2022
DOI: 10.11648/j.ijafrm.20220702.14
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility and Earnings Per Share of Oil and Gas Companies in Nigeria

Abstract: Organizations are operating in a world where they must carry out social, environmental, and economic functions and obligations. All corporations and stakeholders are focusing on the need for social and environmental accounting. This paper studied the impact of corporate social responsibility on the earnings per share of Oil and Gas companies in Nigeria, using ex-post-facto research design, where 8 Oil and Gas companies in Nigeria were examined for a period of 10 years. Total enumeration sampling technique was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 14 publications
(18 reference statements)
1
8
1
Order By: Relevance
“…This finding supported by the results of Mohammed et al, (2016) and Kartadjumana et al ( 2011), who reported that corporate social responsibility expenditure has a significant effect on earnings per share of listed firms. However, this does not support the findings of Owolabi et al, (2022) who reported that CSR has no significant relationship with EPS.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding supported by the results of Mohammed et al, (2016) and Kartadjumana et al ( 2011), who reported that corporate social responsibility expenditure has a significant effect on earnings per share of listed firms. However, this does not support the findings of Owolabi et al, (2022) who reported that CSR has no significant relationship with EPS.…”
Section: Discussioncontrasting
confidence: 99%
“…The results indicated that corporate social responsibility had a positive and significant effect on both return on equity and return on assets, serving as financial performance proxies for listed deposit money banks in Nigeria. Owolabi et al (2022) studied the impact of corporate social responsibility on the earnings per share (EPS) of oil and gas companies in Nigeria, using ex-post-facto research design, where 8 Oil and Gas companies in Nigeria were examined for a period of 10 years. Total enumeration sampling technique was adopted for the study, and descriptive and inferential statistics were used to analyse the data.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…For many years, stakeholders have been clamoring for organizations to be held responsible for the impact of their activities on the environment because of the imbalances in the environmental system. The environmental system is imbalanced, and stakeholders have been demanding that organisations be held responsible for their activities' effects on the environment for a long time [1,2]. The success of every business organization is largely dependent on revenue and the benefits to the environment, society, and economy.…”
Section: Introductionmentioning
confidence: 99%
“…2 nations due to the critical role that the environment plays in the progress and growth of both entities [1]. Environmental accounting as an aspect of corporate social responsibility is a crucial phenomenon that is very vital to the life of any business organization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation